Learning styles and technological preferences among college English course learners: A case study in I-Cats / Herbert Buhod Stephen Naidi - Stephen Naidi, Herbert Buhod (2016)
Technological integrations in English as a Second Language classes are essential needs in the teaching and learning processes in International College of Advanced Technology Sarawak (I-CATS). Unfortunately for the instructors, technological resources were limited to tools and web services on the Internet. The problem with this situation was the suitability of the chosen tools' for different learning styles. To maximize the usability of the technology tool for I-CATS learners' learning style, the study aimed to identify the learning styles of the learners, the technological preferences for various online educational tasks of the learners and the most preferred technological tools for the preferred learning styles. This case study was conducted among all diploma students of I CATS taking various English courses. The population of this study consisted of 496 students from five different programmes and 214 samples were randomly selected from each program. Two sets of instrument were used in this study; the Index of Leaming Style and the Technological Preferences. Descriptive analyses were used to analyze the data from Index of Leaming Styles and Technological Preferences. These data sets were then linked using a method developed by Saeed et al. (2009) in order to match technological tools with the corresponding learning styles. Majority of the respondents' learning styles were Active, Sensing, Visual and Sequential learners. They were moderately Active and Visual learners and fairly well balanced Sensing and Sequential learners. There were three tools frequently ranked in the top three technological preferences namely Email, Chat Application and Facebook Groups. Vodcast was voted for top choice online revision task. All tools mentioned were linked to all of the learners' learning style. This showed Email, Chat Application and Facebook Groups were preferred by I-CATS students with Active, Sensing, Visual and Sequential as their learning styles.